Under an Alaskan sky - Snow, Jennifer (Snow, Jennifer. Wild River ;, 2020)
"Allowing himself to love always seemed too dangerous. Now it might be his only salvation ... Single dad Tank Wheeler has vowed to keep his heart shuttered in the name of keeping his young daughter's life stable. But lately, the chemistry between him and his adrenaline-loving best friend, Cassie Reynolds, has been getting him a little hot under the collar. And then, with one scorching birthday kiss, these best friends are instantly more. Exactly the wrong time for Tank's ex to show up in Wild River, Alaska. Cassie is pretty sure she's having a waking nightmare. Not only is Tank's gorgeous ex hoping to reclaim her family, but a new megastore is threatening the wilderness-adventure business she's spent five years building. But Cassie never backs down from a fight. And now it's time to make the most terrifying leap of her life--and hope that Tank catches her ... before she falls too far."--Provided by publisher.